Predicting Outcome in Combination Treatment of TACE and Camrelizumab for Advanced Hepatocellular carcinoma: Tumor Hypervascularity and Reactive Cutaneous Capillary Endothelial Proliferation - Yin L; Liu KC; Lv WF; Xu SB; Lu D; Zhou CZ; Cheng DL; Gao ZG; Shi CS; Su MX (Dove Medical Press, 2022)
Liang Yin,1,* Kai-Cai Liu,2,* Wei-Fu Lv,1 Shao-Bao Xu,2 Dong Lu,1 Chun-Ze Zhou,1 De-Lei Cheng,1 Zong-Gen Gao,2 Chang-Sheng Shi,2 Ming-Xue Su2 1Department of Radiology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230022, People's Republic of China; 2Infection Hospital, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230000, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei-Fu Lv, Department of Radiology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230000, People's Republic of China, Email weifulv@ustc.edu.cnObjective: To validate the robust predictive values of tumor vascularity and reactive cutaneous capillary endothelial proliferation (RCCEP) in combination treatment of transarterial chemoembolization (TACE) and camrelizumab for patients with advanced hepatocellular carcinoma (HCC) and then select the potential candidates who would survive best from such treatment.Methods: The clinical data of 113 patients with advanced HCC treated with TACE and camrelizumab from January 2019 to December 2021 were analyzed retrospectively. Mann Whitney U-test was used to evaluate the correlation between vascular distribution and RCCEP and tumor response; Kaplan Meier technique was used to evaluate time to progress (TTP) and overall survival (OS), and log rank test was used for comparison; multivariate Cox regression analysis was used to evaluate the related influencing factors.Results: The TTP and OS of TACE combined with carrelizumab in patients with advanced HCC were 7.1 and 14.3 months. Hypervascularity and development of RCCEP were good predictors of TTP (HR 2.561, P < 0.001; HR 1.486, P = 0.032) and OS (HR 2.854, P < 0.001; HR 1.634, P = 0.011). The median TTP and OS of patients with hypervascularity and RCCEP were 10.6 and 19.3 months, which were better than those with only hypervascularity (6.8 months, P = 0.016; 11.6 months, P = 0.003) and only RCCEP (6.2 months, P = 0.039; 13.5 months, P = 0.042), as well as those with neither (3.8 months, P < 0.001; 7.4 months, P < 0.001).Conclusion: Tumor hypervascularity and development of RCCEP were favorable predictive factors for the combination treatment of TACE and carrelizumab, with both of which the patients survived longest and might be the potential candidates.Keywords: hepatocellular carcinoma, transarterial chemoembolization, camrelizumab, vascularity, RCCEP